Endodontic therapy of pathological resorptions of tooth root - Opačić-Galić Vanja; Živković Slavoljub (Serbian Medical Society - Dental Section, Belgrade, 2004)
Pathological resorptions of a tooth root very often represent both a diagnostic and therapeutical problem. The goal of this study was, based on clinical research on a number of pathological resorptions of various types and localization in relation to time, to analyze and evaluate applied endodontic therapy. Clinical research covered 30 patients (40 root canals in total). 18 teeth (22 canal) with external and 12 (18 canal) with internal root resorptions received endodontic therapy. After standard endodontic procedure had been applied (cleaning and canal shaping) calcium hydroxide paste was used as a canal medicament for cases with internal resorptions and calcium hydroxide paste and points for cases with external resorptions. Canal opturations were done by modified technique of lateral condesation applying AH- Plus paste. The obtained results showed that in cases of internal resorption after 12 months, 11 cases were successful and only 1 failure occurred. In case of external resorption, after the same period of time, 15 cases were successful and failures occurred in 3 cases. The success of resorption treatment depends on many factors but, primarily, it depends on time and accuracy of diagnosis and properly applied treatment and root canal opturation.